Identificação química em nível molecular de amostras de maconha por ESI-FT-ICR MS - Nascimento, Iendel Rubio do (2014)
The Cannabis sativa L. is well known in Brazil as "maconha". This is the most consumed drug in this country, proscribed by the Law number 11.343 of 23rd August 2006(called "new drug law) , where all isomers, salts, ethers and esters of ?9Tetrahidrocannabinol (THC), active principle, were proscribed. The method used by the Civil Police of Espírito Santo state to identify the cannabinoids is the test called "colorimetric. It is used by a basic solution of Salt Fast Blue B, which presents results false negatives and false positive. The technic of mass spectrometry of high solution and mass accuracies, ESI(-)FT-ICR MS, allows to detect the main cannabinoids in the form of molecules deprotonated , ions [M-H]. Some ions that can be identified are: [CBN-H]- of m/z 309 (CBN = cannabinol); [THC - H]- of m/z 313 (THC = tetrahidrocannabinol) and [CBD - H]- of m/z 313; [CBC –H]- of 327 (CBC = cannabicromeno); [CBEA - H]- of m/z 345 (CBEA = acid cannabielsóico); [CBNA - H] of m/z 353 (CBEA = acid cannabinólico); [THCA-H] de m/z 357 (THCA = acid tetrahidrocannabinólico); [8a,11-Bis-hydroxy-?9-THC-A - H]- de m/z 389); [?9-THCA +C2H2O - H]- of m/z 357; and dimers with m/z 637, 653, 673, 681, 685 and 717. Identified as contaminants found: [M + H]+: 491; [2M + N + H]+: 819; [3M + N + H]+: 1147, where M = OTHC (328Da C21H28O3) and N is nicotine (C10H14N2 162Da) beyond lidocaine and cocaine. Still some noncannabinóides were identified as: Cannflavino A and B and fatty acids such as palmitic, oleic, linoleic and gammalinolenic acid in the extracts of cannabis seeds. This study has the purpose to identify the chemical profile from samples of cannabis seized by the Civil Police from Espirito Santo state, by ESI(±)-FT-ICR MS.